2014
DOI: 10.4028/www.scientific.net/kem.622-623.912
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Modeling of Shear Strain in Rolling with Velocity Asymmetry in Multi-Roll Calibers

Abstract: Severe plastic deformation is now recognized the most efficient way of producing ultrafine grained metals and alloys. At the present time a lot of severe plastic deformation methods have been proposed and developed. They differ in the deformation schemes. Unlike such severe plastic deformation methods as high pressure torsion and equal-channel angular pressing, rolling with the velocity asymmetry is a continuous process. It helps to solve the problem of the limited length of manufactured bars with semi ultrafi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Previously [12]- [13] it was found that to obtain a high uniform shear strain through the bar thickness during asymmetric three-roll rolling process is necessary: 1) very high contact friction; 2) high elongation ratio; 3) speed ratio of rolls should be equal to elongation ratio per pass. Schematic illustration of the asymmetric threeroll rolling process in a stand with two three-roll calibers located very close to each other is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously [12]- [13] it was found that to obtain a high uniform shear strain through the bar thickness during asymmetric three-roll rolling process is necessary: 1) very high contact friction; 2) high elongation ratio; 3) speed ratio of rolls should be equal to elongation ratio per pass. Schematic illustration of the asymmetric threeroll rolling process in a stand with two three-roll calibers located very close to each other is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Contrary to other SPD methods such as high pressure torsion and equal channel angular pressing, the asymmetric rolling allows to provide the possibility for overcoming the limitation of producing UFG materials with large dimensions due to its continuous feature [8]- [9]. Among the asymmetric rolling processes, the differential speed rolling in which the speeds of the rolls are different, is considered to be the most effective for achieving UFG structure of materials [10]- [13]. Better mechanical properties of wire rod, round bars and hexagonal profiles can be achieved due to large plastic deformation in asymmetric three-roll rolling process.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the finite element simulation it was stated that with reduction Research of influence of different technological factors on metal elongation, shear strain and strain effective in a single three-roll caliber was performed in [11]. One of the problems of asymmetrical three-roll rolling is bending of the bar at the exit from the deformation zone what makes its threading into the next pass more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that shear strain plays a critical role in the grain refinement of aluminium alloys processed by asymmetric rolling [11][12][13][14][15]. The strength of the material continuously increases with increasing the applied shear strain.…”
Section: Introductionmentioning
confidence: 99%